Answer:
The correct answers are, A= 4 and B= 6
Explanation:
let the 1st number be a
let the 2nd number be b
Now from the question, a is 2 less than 3 times b, which is written as follows:
a= 3b-2 ------------> equation 1
Now b is twice the first number less six which is written as follows:
b= 2a-6 ------------> equation 2
Now substituting the value of b in equation 1, we get the following.
a= 3(2a-6)-2
a= 6a -18 -2
6a-a = 18+2
5a=20
a=4
Now putting value of a in equation 2, we get the following:
b= 2(4) -6
b= 12-6
b= 6